Are Quaternary Ammonium Compounds, the Workhorse Disinfectants, Effective against Severe Acute Respiratory Syndrome-Coronavirus-2? - Schrank, Cassandra L; Minbiole, Kevin P C; Wuest, William M (ACS infectious diseases, 2020)
A novel virus named Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) emerged from Wuhan, China in late 2019. Since then, the virus has quickly spread worldwide, leading the World Health Organization to declare it as a pandemic; by the end of April 2020, the number of cases exceeded 3 million. Due to the high infectivity rate, SARS-CoV-2 is difficult to contain, making disinfectant protocols vital, especially for essential, highly trafficked areas such as hospitals, grocery stores, and delivery centers. According to the Centers for Disease Control and Prevention, best practices to slow the spread rely on good hand hygiene, including proper handwashing practices as well as the use of alcohol-based hand sanitizers. However, they provide warning against sanitizing products containing benzalkonium chloride (BAC), which has sparked concern in both the scientific community as well as the general public as BAC, a common quaternary ammonium compound (QAC), is ubiquitous in soaps and cleaning wipes as well as hospital sanitation kits. This viewpoint aims to highlight the outdated and incongruous data in the evaluation of BAC against the family of known coronaviruses and points to the need for further evaluation of the efficacy of QACs against coronaviruses.